Molecular Epidemiology of the Neglected Meat-Borne Pathogen Sarcocystis Spp. in Pigs and Cattle: an Update - Kálmán Imre; Adriana Morar; Mirela Imre; Claudia Corina Sala (Scientific Papers Animal Science and Biotechnologies, 2023)
The host specific Sarcocystis spp., some of them with zoonotic character, is considered cyst-forming intracellular coccidian (Apicomplexa: Sporozoa) parasites. Their life cycle involves carnivores as definitive hosts and herbivores and omnivores as intermediate hosts, including pigs and cattle. The present work aimed to review the worldwide distribution and molecular epidemiology of Sarcocystis spp. in cattle and pigs, processing PubMed retrieved relevant scientific papers, published in the new century and based on molecular tools. Mainly, prevalence values of the infections according to countries and geographical regions; incriminated Sarcocystis spp. and their isolation sources together with the targeted genes and used primers, as well as public health significance of the isolates, are presented. The published summarized results may be useful for epidemiologists and public health specialists.